2019
DOI: 10.1021/acsnano.8b08411
|View full text |Cite
|
Sign up to set email alerts
|

Watching Dynamic Self-Assembly of Web Buckles in Strained MoS2 Thin Films

Abstract: Thin films with large compressive residual stress and low interface adhesion can buckle and delaminate from relatively rigid substrates, which is a common failure mode of film/substrate interfaces. Current studies mainly focused on the geometry of various buckling patterns and related physical origins based on a static point of view. However, fundamental understanding of dynamic propagation of buckles, particularly for the complicated web buckles, remains challenging. We adopt strained two-dimensional MoS2 thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(56 citation statements)
references
References 43 publications
2
54
0
Order By: Relevance
“…In addition, most reported wrinkling patterns in the experiments are not perfect hexagons and contains pentagons and heptagons, which can be viewed as defects (e.g., disclinations, dislocations, and grain boundaries) if we treat hexagons as perfect crystal lattices. Very recently, hexagonal patterns down to micrometers were also reported in nanoscale strained MoS2 film on a sapphire substrate [Ren et al, 2019].…”
Section: Introductionmentioning
confidence: 90%
“…In addition, most reported wrinkling patterns in the experiments are not perfect hexagons and contains pentagons and heptagons, which can be viewed as defects (e.g., disclinations, dislocations, and grain boundaries) if we treat hexagons as perfect crystal lattices. Very recently, hexagonal patterns down to micrometers were also reported in nanoscale strained MoS2 film on a sapphire substrate [Ren et al, 2019].…”
Section: Introductionmentioning
confidence: 90%
“…In addition, the researchers have found that the intrinsic tensile strain (0.15–1.37%) was also introduced in CVD grown-monolayer MoS 2 [ 113 , 115 , 117 , 118 , 119 , 122 ]. This intrinsic tensile strain is caused by the mismatch of thermal expansion coefficients [ 72 , 73 , 113 , 115 , 116 , 117 , 121 ]. Interestingly, whether through flexible substrate [ 104 ] or thermal mismatch [ 72 , 73 ], the strain state of MoS 2 materials can be further mediated by creating buckles [ 72 , 73 , 104 , 105 , 114 , 121 , 123 , 124 ].…”
Section: Experimental Progress Of Strain-mediated Magnetismmentioning
confidence: 99%
“…This intrinsic tensile strain is caused by the mismatch of thermal expansion coefficients [ 72 , 73 , 113 , 115 , 116 , 117 , 121 ]. Interestingly, whether through flexible substrate [ 104 ] or thermal mismatch [ 72 , 73 ], the strain state of MoS 2 materials can be further mediated by creating buckles [ 72 , 73 , 104 , 105 , 114 , 121 , 123 , 124 ].…”
Section: Experimental Progress Of Strain-mediated Magnetismmentioning
confidence: 99%
See 1 more Smart Citation
“…The strain effect of 2D materials is also related to the lattice vibration and crystal orientation, resulting in the change of optical properties such as PL and Raman shift . It is well known that the diversification of bandgap and light emission energy is owing to the electronic configuration and energy levels based on the change of atomic structure by applied strain.…”
Section: Stretching and Bending Of 2d Materialsmentioning
confidence: 99%